How to Teach English Entrant for Binus University Students Using A Cell Group Method Supported by Binusmaya - Melania Wiannastiti (Bina Nusantara University, 2011)
Teaching English Entrant, the first level of General English lecture for BINUS University students, needs a specific method because normally the number of students in one class is more than 50 students. Besides, the four skills of language and business communication have to be taught simultaneously in one semester. This paper is aimed to describe one method used at BINUS University to teach English Entrant classes: Cell Group method which students are divided into cell groups. This method is supported by Binusmaya, an online resource used in teaching learning at BINUS University. Through this resource, each member of the cells has the opportunity to access Binusmaya forum where he/she can upload, download, share and discuss material or problems raised. Each cell is also responsible to write reports about its activities. Based on the reports, the teacher who has a role as a moderator and source in both Binusmaya forum and classroom has to lead the cells discussion in the classroom.